Adverse effects of frailty on social functioning in older adults: Results from the Longitudinal Aging Study Amsterdam. (January 2016) - Hoogendijk, Emiel O.; Suanet, Bianca; Dent, Elsa; Deeg, Dorly J.H.; Aartsen, Marja J.
Highlights: This study investigated the effects of frailty on social functioning in older adults. Frail older adults have a smaller network size and higher levels of loneliness. Frailty is associated with an increase in loneliness over 3 years of follow-up. Social vulnerability of physical frail older adults should be taken into account in the care for this population. Abstract: Objectives: The aim of this study was to examine the association between physical frailty and social functioning among older adults, cross-sectionally and prospectively over 3 years. Study design: The study sample consisted of 1115 older adults aged 65 and over from two waves of the Longitudinal Aging Study Amsterdam, a population based study. Main outcome measures: Frailty was measured at T1 (2005/2006) using the criteria of the frailty phenotype, which includes weight loss, weak grip strength, exhaustion, slow gait speed and low physical activity. Social functioning was assessed at T1 and T2 (2008/2009) and included social network size, instrumental support, emotional support, and loneliness. Results: Cross-sectional linear regression analyses adjusted for covariates (age, sex, educational level and number of chronic diseases) showed that pre-frail and frail older adults had a smaller network size and higher levels of loneliness compared to their non-frail peers. Longitudinal linear regression analyses adjusted for covariates and baseline social functioning showed that frailty was associated with an increase in loneliness over 3 years. However, the network size and levels of social support of frail older adults did not further decline over time. Conclusions: Frailty is associated with poor social functioning, and with an increase in loneliness over time. The social vulnerability of physical frail older adults should be taken into account in the care provision for frail older adults.